Knowledge, practice pattern and attitude toward asthma management amongst physicians from Nepal, Malaysia, Lebanon, Myanmar and Morocco. (3rd July 2021) - Chokhani, Ramesh; Razak, Abdul; Waked, Mirna; Naing, Win; Bakhatar, Abdelaziz; Khorani, Urvi; Gaur, Vaibhav; Gogtay, Jaideep
Abstract: Objective: This survey aimed to understand the physicians' practice pattern and challenges faced while treating their patients with asthma in five countries-Malaysia, Nepal, Myanmar, Morocco and Lebanon. Methods: Questionnaire-based data was gathered from internal medicine doctors (209), general practitioners (206), chest physicians (152) and pediatricians (58) from 232 locations from across the five countries. Results: Of the 816 physicians, 374 physicians encountered at least 5 asthma patients daily. Approximately, 38% physicians always used spirometry for diagnosis and only 12% physicians always recommended Peak flow meter (PFM) for home-monitoring. Salmeterol/fluticasone (71%) followed by formoterol/budesonide (38%) were the most preferred ICS/long-acting beta2 -agonists (LABA); Salbutamol (78%) was the most preferred reliever medication. 60% physicians said >40% of their patients were apprehensive to use inhalers. 72% physicians preferred a pressurized metered-dose inhaler (pMDI) to a dry powder inhaler (DPI) with only a third of them using a spacer with the pMDI. 71% physicians believed that using similar device for controller and reliever can be beneficial to patients. Skipping medicines in absence of symptoms (64%), incorrect inhaler technique (48%) and high cost of medication (49%) were considered as major reasons for non-adherence by most physicians. Incorrect inhaler technique (66%) and nonadherence (59%) were considered the most common causes of poor asthma control. Conclusions: There are opportunities to improve the use of diagnostic and monitoring tools for asthma. Non-adherence, incorrect inhaler technique and cost remain a challenge to achieve good asthma control. Asthma education, including correct demonstration of inhaler, can potentially help to improve inhaler adherence.